AB0345 Does iron deficiency contribute to fatigue of patients with rheumatoid arthritis without anaemia?. (12th June 2018) - Vidal, F.; Gillibert, A.; Quillard, M.; Fardellone, P.; Pouplin, S.; Vittecoq, O.; Lequerré, T.
Abstract : Background: Iron deficiency (ID) without anaemia is a cause of fatigue, which is itself a recurring complaint of patients with rheumatoid arthritis (RA). Objectives: The objective of the study was to determine the prevalence of ID in patients with RA without anaemia and to analyse the relationship between ID with fatigue, disease activity and depression. Methods: This study included patients with RA according to the ACR/ EULAR 2010 classification criteria (American College of Rheumatology/European League Against Rheumatism) followed up in the Rheumatology Department of Rouen University Hospital and who had a haemoglobin >12.5 g/dl. Patients were either from the single-centre monocentric longitudinal cohort or from the seventh visit of the VErA (Very Early Arthritis) High-Norman regional cohort. For each patient of the longitudinal cohort, DAS 28 ESR (Disease Activity Score – erythrocyte sedimentation rate) the FACIT – version 4 fatigue score (Functional Assessment of Chronic Illness Therapy) and a depression score (Hospital Anxiety and Depression Scale) were collected. Serum ferritin, transferrin, serum iron and saturation coefficient of transferrin were measured for each patient. ID was defined as serum ferritin <50 µg/L. Results: One hundred and forty-one patients were included in the longitudinal cohort (78.7% women, mean age 13.50±9.51 years, positive rheumatoid factor and anti-citrullinated peptide antibodies in 83.6% and 86.5% of patients) and 74 RA patients from the VERA cohort (70.3% women, mean disease duration 2.74±0.24 years). The prevalence of ID was 15.6% in the longitudinal cohort (n=22/141) and 14.9% in the VErA cohort (n=11/74). In the longitudinal cohort, there were no significant differences between ID patients and non-deficient patients in fatigue (mean FACIT of 27.80±12.4 vs. 32.3±12.0; p=0.14), disease activity (mean DAS 28 VS 2.85±1.38 vs. 2.96±1.48; p=0.74) and depression (mean HAD score 5.86±4.12 vs. 5.80±3.84; p not calculated). Conclusions: The prevalence of ID without anaemia was similar between early and old RA and was similar to that of the general French adult population (15.5%). 1 ID does not appear to be a major cause of fatigue in RA and does not affect the activity of the disease. The search for an ID is of limited value in exploring fatigue of RA patients. Reference: [1] Institut National de Veille Sanitaire. Etude Nationale Nutrition santé, ENNS 2006. Disclosure of Interest: None declared